Gallic Acid Derivatives Propyl Gallate and Epigallocatechin Gallate Reduce rRNA Transcription via Induction of KDM2A Activation - Yuji Tanaka; Makoto Tsuneoka (Biomolecules, 2021)
We previously reported that lysine-demethylase 2A (KDM2A), a Jumonji-C histone demethylase, is activated by gallic acid to reduce H3K36me2 levels in the rRNA gene promoter and consequently inhibit rRNA transcription and cell proliferation in the breast cancer cell line MCF-7. Gallic acid activates AMP-activated protein kinase (AMPK) and increases reactive oxygen species (ROS) production to activate KDM2A. Esters of gallic acid, propyl gallate (PG) and epigallocatechin gallate (EGCG), and other chemicals, reduce cancer cell proliferation. However, whether these compounds activate KDM2A has yet to be tested. In this study, we found that PG and EGCG decreased rRNA transcription and cell proliferation through KDM2A in MCF-7 cells. The activation of both AMPK and ROS production by PG or EGCG was required to activate KDM2A. Of note, while the elevation of ROS production by PG or EGCG was limited in time, it was sufficient to activate KDM2A. Importantly, the inhibition of rRNA transcription and cell proliferation by gallic acid, PG, or EGCG was specifically observed in MCF-7 cells, whereas it was not observed in non-tumorigenic MCF10A cells. Altogether, these results suggest that the derivatization of gallic acid may be used to obtain new compounds with anti-cancer activity.